2012
DOI: 10.1007/s00464-012-2256-x
|View full text |Cite
|
Sign up to set email alerts
|

Refractory and new-onset diabetes more than 5 years after gastric bypass for morbid obesity

Abstract: This is the first investigation, to the best of our knowledge, to underscore the correlates of refractory and NOD within the bariatric context. Further studies are recommended as such information could be valuable for patient selection, prognostic scoring, and outcome monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Our results may partially be explained by the fact that on multivariable analysis, lower preoperative BMI was independently observed to be associated with diabetes responsive to surgery. Previous studies have observed similar associations between preoperative weight (25), postoperative weight loss (21), and diabetic cure. This association is presumed to occur secondary to changes in gut hormonal physiology (i.e., incretins, ghrelin, and glucagon-like peptide-1) induced by and in addition to the restrictive and upper gastrointestinal excluding properties intrinsic to gastric bypass (20, 3042).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results may partially be explained by the fact that on multivariable analysis, lower preoperative BMI was independently observed to be associated with diabetes responsive to surgery. Previous studies have observed similar associations between preoperative weight (25), postoperative weight loss (21), and diabetic cure. This association is presumed to occur secondary to changes in gut hormonal physiology (i.e., incretins, ghrelin, and glucagon-like peptide-1) induced by and in addition to the restrictive and upper gastrointestinal excluding properties intrinsic to gastric bypass (20, 3042).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have observed similar if not slightly higher percentages of diabetic cure rates ranging from 41–100% at 1-year (1823), 75% at 2-year (24), 44–88% at 5-year (2528), and 71–89% at 10-year follow-up (79). One possible explanation for this discrepancy may involve attrition rates, which are known to impact observed health outcomes (26, 29).…”
Section: Discussionmentioning
confidence: 69%
“…Recurrence rates of T2 DM come 5-10 years later, in a higher proportion (25-40%) [8]. This means that the initial promise of 470% "cure" of T2 DM regresses to 40-50%, compared to 490% with DS.…”
Section: Q6mentioning
confidence: 96%
“…At 3 years after RYGB, T2D re-emerged or worsened in 24% of diabesity patients [48] and in 35% at 5 years post surgery [49]. Other studies report that recurrence of T2D after initial surgical remission was evident in 19% within a 5 --9-year follow-up range across various procedures [15] and 31.4% within 7 --9 years after RYGB [50]. Among morbidly obese patients with remission of diabetes at 2 years after metabolic/bariatric surgery involving RYGB, AGB and other procedures, T2D was reported to have reoccurred in 50% by 10 years' follow-up [30,46].…”
mentioning
confidence: 97%